Faktor Risiko Terjadinya Anemia pada Ibu Hamil - Odi Lodia Namangdjabar; Pius Weraman; Ignasensia Dua Mirong (Journal of Telenursing (JOTING), 2022)
This study aims to determine the risk factors for anemia in pregnant women at the Baumata Health Center, Kupang Regency, in 2022. The method used is observational with a cross-sectional approach. The results showed that the number of pregnant women who had a risky age was 28 respondents (63.8%), pregnant women with a risky pregnancy interval were 21 respondents (51.2%), pregnant women with nutritional status who were at risk of Chronic Energy Deficiency (KEK) totaled 25 respondents (61%) and pregnant women with less knowledge about anemia amounted to 24 respondents (58.5%). In conclusion, there is a significant relationship between age, gestational distance, nutritional status and knowledge with the incidence of anemia in pregnant women. Keywords: Anemia, Pregnant women, Pregnancy Distance, Knowledge, Nutritional Status, Age